2007
DOI: 10.2307/25549716
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Standard Days Method: Expanding Family Planning Options in Rwanda

Abstract: The Standard Days Method is a simple fertility awareness-based method of family planning that helps women identify the days each cycle when they are most likely to conceive. Couples who wish to prevent pregnancy avoid unprotected intercourse on these days. The method was introduced in 13 sites in Rwanda, a nation with a high level of unmet need for family planning. This was the first time the method was introduced into regular service delivery, without the rigorous follow-up of a study setting. Users of the St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 1 publication
1
38
1
Order By: Relevance
“…Of those 36, 10 reported having experienced two or more menstrual cycles that fell outside the 26–32-day range. This finding is consistent with studies of SDM efficacy in Bolivia, Peru and The Philippines,6 Rwanda12 and Istanbul 13. A stringent, ongoing menstrual cycle monitoring protocol must be followed until the woman has two cycles that fall outside the 26–32-day range within a 1-year timeframe.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Of those 36, 10 reported having experienced two or more menstrual cycles that fell outside the 26–32-day range. This finding is consistent with studies of SDM efficacy in Bolivia, Peru and The Philippines,6 Rwanda12 and Istanbul 13. A stringent, ongoing menstrual cycle monitoring protocol must be followed until the woman has two cycles that fall outside the 26–32-day range within a 1-year timeframe.…”
Section: Discussionsupporting
confidence: 80%
“…These studies suggest that the SDM tends to be perceived by couples as being an effective, easy, low/no cost and safe alternative family planning option for those dissatisfied with their previous family planning method(s) and those who are concerned about the side effects of other contraceptive methods. Contrary to the above findings, studies conducted in Rwanda,12 and in four of the study sites of the multisite operational research on the SDM (Benin, El Salvador, Honduras and India),10 demonstrated that the majority of the study participants had never used any contraceptive methods before adopting the SDM. In the present study only 20% of the study participants had not reported previous use of family planning methods.…”
Section: Discussioncontrasting
confidence: 75%
“…Sinai says that we "ignored at least eight relevant articles" that oppose our views. Not one of the citations she provides opposes our findings, and six do not even contain information about effectiveness: four are studies already mentioned above [2][3][4][5]; two more by Lundgren et al do not measure effectiveness, one measures uptake of SDM in three sites [6], and one knowledge and attitudes [7]. One article [8] provides figures from intervention studies, not typical use (see also point 7 below).…”
mentioning
confidence: 70%
“…Hardee et al state "several studies show similar rates with typical use" but do not provide any evidence for this claim. Instead, they provide two irrelevant citations: Blair et al [2] report on a qualitative study; Kalaca et al [3] provide some information about pregnancies in their very small sample but do not report effectiveness, which the study was not designed to measure.…”
mentioning
confidence: 99%
“…Some programmes may decide to offer the SDM because it brings new couples to family planning, and provides a bridge to other modern family planning methods 1213. Other programmes may be reluctant to offer the method if they perceive that it will be used only for a short time, and therefore integration may not be worth the effort.…”
Section: Discussionmentioning
confidence: 99%